DIABETES: A LITERATURE REVIEW - Silva Costa Barros, Sarah; Lívio Gomes Moura, Pedro; Luíza de Lima Gonçalves, Ana; Celso Fernandes Monteiro, Mateus; Maria Neves Silva Souza, Elizabeth; Almeida Saraiva, Júlia; Alberto Feitosa dos Santos, Carlos; Ferreira de Miranda, Izabel; Gabriely Machado de Albuquerque, Hellen; Oliveira Ferro, Gabriel (Health and Society, 2022)
Diabetes mellitus arises as a result of insulin resistance or a decrease in its production. This work consists of analyzing the various immunological and pathophysiological factors of diabetes mellitus. This is a bibliographic, descriptive, qualitative review, having as a source of researching books, guidelines and articles in the authors’ personal collection and internet. In the case of type I diabetes mellitus, its development occurs through genetic alterations located mainly on chromosome 6, resulting in immunological reactions mediated by inflammatory cytokines such as IL-6 and TNF-α in the sense of directly attacking the pancreatic islets, reducing the population of producing cells. of insulin. On the other hand, in type II diabetes mellitus, it is the adipose tissue, which secretes the same inflammatory cytokines that act by antagonizing insulin, despite a strong association with heredity and some genetic factor that has not yet been clarified. This increased reactivity of the immune system also impacts in association with other immune-mediated diseases, a more severe condition and an increase in the inflammatory response in infectious diseases. We conclude from the research carried out, the importance of the genetic and immunological factor involved in diabetes mellitus opening doors for the creation of new treatments and also greater care for patients given their greater morbidity.